Decoding Land Use Conflicts: Spatiotemporal Analysis and Constraint Diagnosis from the Perspectives of Production–Living–Ecological Functions - Yong Liu; Rui Xu; Jixin Yang; Xinpeng Xie; Xufeng Cui (Land)
Exploring the intensity and constraint factors of land use conflicts provides essential insights for efficient land use planning. Currently, China’s spatial development is gradually transitioning towards the coordinated development of production, living, and ecological functions (PLEFs). Previous studies have typically focused on land use conflicts from a micro perspective, examining conflicts between production, living, and ecological land uses at a fine scale. There is limited research from a macro perspective that conducts a theoretical analysis based on the production, living, and ecological functions of land use conflicts themselves. In addition, existing studies primarily analyze the influencing factors of land use conflicts, with limited literature directly addressing the constraint factors of land use conflicts. This study focuses on 12 prefecture-level cities in Hubei Province, China, using data from 2010 to 2020. It categorizes land use conflicts at the macro level into production perspective, living perspective, and ecological perspective conflicts. For each of these conflict perspectives, different pressure, state, and response indicators are introduced. This approach leads to the development of a theoretical framework for analyzing land use conflicts at the macro level. On this basis, a spatiotemporal evolution analysis of land use conflicts was conducted. Additionally, using a constraint factor diagnosis model, the study analyzed the constraint factors of land use conflicts at the macro level across cities, leading to the following research conclusions: (1) the land use conflicts from the production and living perspectives in the 12 prefecture-level cities of Hubei showed an upward trend from 2010 to 2020, while the land use conflicts from the ecological perspective exhibited a downward trend; (2) during the study period, Wuhan exhibited the highest intensity of land use conflicts from both the production and living perspectives, while Ezhou experienced the highest intensity of land use conflicts from the ecological perspective for most of the study period; (3) the main constraining factors of land use conflicts from the production perspective in the 12 prefecture-level cities of Hubei are population density, average land GDP, and effective irrigation rate. The primary constraining factors of land use conflicts from the living perspective are population density, urbanization rate, and average land real estate development investment. The main constraining factors of land use conflicts from the ecological perspective are population density, average land fertilizer input, and effective irrigation rate. This study constructs a new theoretical framework for land use conflict assessment at the macro level, providing a novel approach for studying land use conflicts at the macro scale.